2018
DOI: 10.1158/1078-0432.ccr-17-2439
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Activity, and Biomarkers of SHR-1210, an Anti-PD-1 Antibody, for Patients with Advanced Esophageal Carcinoma

Abstract: The current management of advanced esophageal squamous cell carcinoma (ESCC) remains unsatisfactory. We investigated the safety, efficacy, and biomarkers of SHR-1210, an anti-PD-1 antibody, in patients with recurrent or metastatic ESCC. This study was part of a phase I trial in China. Patients with advanced ESCC who were refractory or intolerant to previous chemotherapy were enrolled. Eligible patients received intravenous SHR-1210 at a dose of 60 mg, with escalation to 200 and 400 mg (4-week interval after fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
161
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(184 citation statements)
references
References 23 publications
12
161
1
Order By: Relevance
“…Additionally, pembrolizumab in 18 PD‐L1‐positive ESCC patients demonstrated a promising ORR of 28%, while in 23 patients, the median PFS and OS rates were 1.8 and 7.0 months, respectively, including squamous and adenocarcinoma histology . Moreover, we reported the safety and efficacy of treatment with a novel PD‐1 antibody, camrelizumab, from a phase I study . Continued follow‐up of our ESCC cohort verified encouraging ORRs and PFS, consistent with the results of previous reports, while the OS was different, mainly as a result of the variance in patient selection …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, pembrolizumab in 18 PD‐L1‐positive ESCC patients demonstrated a promising ORR of 28%, while in 23 patients, the median PFS and OS rates were 1.8 and 7.0 months, respectively, including squamous and adenocarcinoma histology . Moreover, we reported the safety and efficacy of treatment with a novel PD‐1 antibody, camrelizumab, from a phase I study . Continued follow‐up of our ESCC cohort verified encouraging ORRs and PFS, consistent with the results of previous reports, while the OS was different, mainly as a result of the variance in patient selection …”
Section: Discussionsupporting
confidence: 89%
“…However, the clinical benefit is restricted to only a fraction of patients, and biomarkers for both response and survival are under exploration. We previously reported that high PD‐L1 expression, mutation load, and potential mutation‐associated neoantigen count are associated with a better response . In the KEYNOTE‐028 trial, six‐gene interferon‐γ gene expression signature analysis indicated that higher interferon‐γ composite scores may predict delayed progression and an increased response .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Interstitial lung disease is an immune-mediated toxicity that resulted in the only drug-related death in this study, and this is consistent with the safety profile in a previous phase 1 study of nivolumab. 13,14 Interstitial lung disease is an immune-mediated toxicity that resulted in the only drug-related death in this study, and this is consistent with the safety profile in a previous phase 1 study of nivolumab.…”
Section: Discussionsupporting
confidence: 89%
“…According to the latest released results of NCT02742935 , treatment with SHR1210 in advanced/refractory ESCC resulted in an objective response rate of 33.3% and a median progression‐free survival of 3.6 months. The most common TRAEs were reactive capillary hemangiomas (76.7%, 23/30), which was believed to be related to the activation of vascular endothelial growth factor (VEGF)/VEGF receptor pathway.…”
Section: Domestic‐developed Agentsmentioning
confidence: 99%